Effects of inclusion of Gd₂O₃ microparticles and Gd₂O₃ nanoparticles on elastic, linear and nonlinear optical properties of zinc borotellurite glasses - Chua, Ee Von (2017)
The purpose of this present work is to study the effect of Gd2O3 and Gd2O3 NPs on elastic, linear and nonlinear optical properties of zinc borotellurite glass system. Zinc borotellurite glass system doped with gadolinium oxide (Gd2O3) and gadolinium oxide nanoparticles (Gd2O3 NPs) with chemical formula {[(TeO2)70(B2O3)30]70(ZnO)30}1-x (RE2O3)x (where x = 1.0, 2.0, 3.0, 4.0 and 5.0 mol% and RE2O3 = Gd2O3 and Gd2O3 NPs) were fabricated using conventional melt quenching technique. XRD results confirmed the amorphousity of the glass samples. The infrared spectra of the glass systems indicate the existence of TeO3, TeO4, BO3 and BO4 vibrational groups. The presence of Gd2O3 NPs was proven from TEM images. The longitudinal ultrasonic velocities vary from 3908 to 4076 m/s and 3883 to 4042 m/s for Gd2O3 and Gd2O3 NPs doped zinc borotellurite glasses, respectively while the shear ultrasonic velocities vary from 2222 to 2277 m/s and 2251 to 2282 m/s for Gd2O3 and Gd2O3 NPs doped zinc borotellurite glasses, respectively. The observed change in ultrasonic velocities shows that there is a substantial change in the structure of the glass. The elastic moduli (longitudinal modulus (L), shear modulus (G), bulk modulus (K) and Young’s modulus (E)) obtained for Gd2O3 doped zinc borotellurite glass system increase from 55.44 to 81.35 GPa, 18.39 to 25.00 GPa, 30.92 to 48.02 GPa and 46.02 to 63.90 GPa, respectively. In addition, the elastic moduli (L, G, K and E) for Gd2O3 NPs doped zinc borotellurite glasses increase from 55.44 to 79.45 GPa, 18.39 to 26.68 GPa, 30.92 to 43.87 GPa and 46.05 to 66.55 GPa, respectively. The increase elastic moduli indicate that the rigidity of the glass increases. The experimental results showed that the elastic properties system depend on the composition of the glass system and the role of Gd2O3 and Gd2O3 nanoparticles inside the glass network. The direct and indirect optical band gap energy increases from 3.239 to 3.519 eV and 2.587 to 3.172 eV for Gd2O3 doped zinc borotellurite glasses whereas the direct and indirect optical band gap energy for Gd2O3 NPs doped zinc borotellurite glasses decrease from 3.301 to 2.985 eV and 2.790 to 2.386 eV, respectively. In addition, the refractive index of Gd2O3 doped glasses decrease from 2.518 to 2.352 while an increasing trend from 2.456 to 2.551 is observed in Gd2O3 NPs doped zinc borotellurite glasses. It was found that the optical band gap and refractive index of Gd2O3 doped glasses show opposite behaviour to Gd2O3 NPs doped glass systems. This might be attributed to the presence of nanoparticles having large surface area which form high density states that can serve to trap charge carriers. The nonlinear refractive index of the glass systems showed self-focusing behaviour and reverse saturable absorption (RSA) or two-photon absorption were observed for nonlinear optical absorption. The values of nonlinear refractive index vary from 0.632 to 0.943 x 10-14 cm2/W and 0.266 to 1.515 x 10-14 cm2/W for Gd2O3 and Gd2O3 NPs doped glass systems, respectively. Moreover, the values of nonlinear absorption coefficient vary from 0.616 to 0.747 cm/GW and 0.660 to 0.729 cm/GW for both Gd2O3 and Gd2O3 NPs doped zinc borotellurite glasses, respectively. The variation of nonlinear optical parameters was due to the formation of TeO4, the presence of lone pairs electron in TeO4 and the effect of large Gd3+ ion as well as the reduction in size of bulk materials. The results obtained from z-scan suggested that the presently studied glass systems can be used for design of nonlinear optical materials.